2016
DOI: 10.1103/physrevb.94.020401
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of a propagating spin-wave packet created by an ultrashort laser pulse in a thin film of a magnetic metal

Abstract: Coherent spin-wave generation by focused ultrashort laser pulse irradiation was investigated for a permalloy thin film at micrometer scale using an all-optical space and time-resolved magneto-optical Kerr effect. The spin-wave packet propagating perpendicular to magnetization direction was clearly observed, however that propagating parallel to the magnetization direction was not observed. The propagation length, group velocity, center frequency, and packet-width of the observed spin-wave packet were evaluated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 28 publications
3
23
0
2
Order By: Relevance
“…18, which reported monotonic magnetization reversal even in Gd22% samples, we confirmed that the magnetization response of the sample depends not only on the T A value of its Gd-Fe-Co layer, but also on its multilayer structure. Although the quasi-spinwaves observed in our experiments may not qualify as coherent magnons, [9][10][11][12] we achieved an unprecedentedly large precession angle of the induced waves (on the order of 10°). Considering that low-frequency precession is allowed within the uncertainty of our present experiment, and knowing that anomalous behavior occurs in samples with specific heat conduction, experimental and theoretical searches for spin-phonon coupling 19,20) may also be worthwhile.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…18, which reported monotonic magnetization reversal even in Gd22% samples, we confirmed that the magnetization response of the sample depends not only on the T A value of its Gd-Fe-Co layer, but also on its multilayer structure. Although the quasi-spinwaves observed in our experiments may not qualify as coherent magnons, [9][10][11][12] we achieved an unprecedentedly large precession angle of the induced waves (on the order of 10°). Considering that low-frequency precession is allowed within the uncertainty of our present experiment, and knowing that anomalous behavior occurs in samples with specific heat conduction, experimental and theoretical searches for spin-phonon coupling 19,20) may also be worthwhile.…”
mentioning
confidence: 90%
“…7,8) However, the responses of materials to laser pulses are not limited to magnetization switching. The electric and magnetic field vectors of laser beams can interact strongly with electrons in materials, generating coherent magnons [9][10][11][12] and plasmons. 13) Laser-triggered superdiffusive spin currents have transiently modified the equilibrium spin populations in specially designed magnetic structures.…”
mentioning
confidence: 99%
“…Traditionally, the investigation of SWs and their damping are performed using ferromagnetic resonance (FMR) techniques [6,7]. Alternatively, femtosecond laser pulses have been recently presented as an important tool to trigger SWs in a wide variety of conducting [8][9][10], semiconducting [11][12][13][14][15], and insulating [16][17][18][19][20][21] magnetic materials, as well as probing their real-time dynamics with a very high spatiotemporal resolution using femtosecond magneto-optical pump-probe techniques [22][23][24][25][26]. These highly resolved spatiotemporal investigations provide important opportunities to improve the understanding of SWs, with the aim * madeb@uni-potsdam.de of manipulating their dynamics at the fastest speed and in the most efficient way.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, while propagating spin waves does not require current flow, their excitation, which is typically achieved using optical pulses [4][5][6][7][8] , the Oested field of microwave strip-lines [9][10][11] , or via spin torque effects [12][13][14] , is more problematic. Here, the former approach is limited by the difficulties of miniaturizing powerful laser systems and optics, while the latter two cases inherently require current flow.…”
mentioning
confidence: 99%